VD_FINDINFO HC / 2025 / 293 vom 16. Mai 2025 - VD Tribunal cantonal (2025)
PRESCRIPTION, AIASSURANCE, LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, INCAPACITÉ DE TRAVAIL | 8 CC, 127 CO, 247 al. 2 CPC (CH), 55 CPC (CH)